(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
This paper displays linear and nonlinear model for double inverted pendulum system depended on Lagrange equation and the system response for linear and nonlinear of DIPS are noted and analyzed. The inverted pendulum has been advanced for a laboratory experiments. The essential variance between the linear and nonlinear equation is present. This analysis is useful for progress of effective controller for a DIPS.